2011
DOI: 10.1177/1076029611416640
|View full text |Cite|
|
Sign up to set email alerts
|

Ancillary Findings on CT Pulmonary Angiograms and Abnormalities on Chest Radiographs in Patients in Whom Pulmonary Embolism was Excluded

Abstract: To determine whether chest radiographs identify some abnormalities not shown as ancillary findings on computed tomography(CT) pulmonary angiograms of patients in whom pulmonary embolism (PE) was excluded. This was a retrospective study of reports of negative 64-detector CT pulmonary angiograms and chest radiographs. Among 332 patients with no PE, pulmonary parenchymal disease was shown in 60 (18%) only on standard chest radiographs, and pleural or pericardial disease was shown in 17 (5%) only on chest radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…Therefore, we built upon the methodology used by Richman et al [18], the largest study to date in this field, and simplified that categorization scheme into two clinically relevant groups: actionable Type 1 findings requiring follow-up and the combination of non-actionable Type 2 findings requiring no follow-up and exams that were totally normal Type 3 (Table 1). Using these groups to sort the CTA data, we observed a large amount of variability in the incidence of Type 1 (17-67%) and Type 2 + Type 3 findings on CTA (33-83%) extracted from the prior literature (Table 2) [18][19][20][21]. Surprisingly, however, we found that the percentages of Type 1 and the combined categories of Type 2 and Type 3 findings found at MRA in this study were equivalent to those reported by Richman et al [18] ( Table 3).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, we built upon the methodology used by Richman et al [18], the largest study to date in this field, and simplified that categorization scheme into two clinically relevant groups: actionable Type 1 findings requiring follow-up and the combination of non-actionable Type 2 findings requiring no follow-up and exams that were totally normal Type 3 (Table 1). Using these groups to sort the CTA data, we observed a large amount of variability in the incidence of Type 1 (17-67%) and Type 2 + Type 3 findings on CTA (33-83%) extracted from the prior literature (Table 2) [18][19][20][21]. Surprisingly, however, we found that the percentages of Type 1 and the combined categories of Type 2 and Type 3 findings found at MRA in this study were equivalent to those reported by Richman et al [18] ( Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…This method is similar to the Richman category A-findings requiring immediate follow up and Richman category B-findings requiring follow up to prevent significant morbidity in subsequent weeks or months as subcategories into one new Category-Type 1 and the Richman Category C-findings requiring no immediate action into this study's Type 2 and Richman Category D-inderminant findings along with all normal exams into a third group of findings for this study-Type 3. The single most important of the many findings derived from the final report of each case were categorized by consensus of two radiologists (JA and MS) using a very complete rubric derived from the exiting CTA literature for all of the previously listed ancillary findings (Table 2) [18,32]. The first category (Type 1) includes all radiology report findings that required some form of follow-up by the referring clinician.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations